Self-perceived general health among community-dwelling Portuguese older adults: do men and women differ' - Alarcão, V.; Costa, J.; Madeira, T.; Peixoto-Plácido, C.; Fernandes, E.; Sousa-Santos, N.; Santos, O.; Nicola, P. J.; Lopes, C.; Gorjão-Clara, J. (Ageing and Society, 2022)
Evidence on how gender intersects with relevant social constructs in later phases of life is scarce. This investigation examined gender inequalities in perceived health status (self-perceived general health; SPGH) by Portuguese elderly community-dwellers while considering psycho-social and socio-demographic determinants. This study used data from a representative sample of community-dwellers aged ≥65 years (N = 920), who were enrolled in the Portuguese Elderly Nutritional Status Surveillance System (PEN-3S) project. Associations between SPGH and socio-demographic and psycho-social variables, functionality and self-reported morbidity were tested; indirect effects of relevant predictors on SPGH were also tested using a bootstrap method. Gender inequalities in health were found: women significantly rated their health worse than men; overall, participants rated their health as fair. Education, functional status, depression symptoms and self-reported morbidity significantly predicted SPGH among women, whereas only the latter two were associated with SPGH among men. For both genders, depression was the strongest predictor of SPGH. Mediation analyses detected indirect effects of cognitive function and loneliness feelings on SPGH among older adults. Results herein provide insights on the predictive role of psycho-social variables on SPGH and support the need for considering the context when addressing the correlates of SPGH among Portuguese older adults. Altogether, these findings might support cost-effective interventions targeting the most vulnerable groups of the population to inequalities in health and its predictors.